(untitled) (Tidsskrift for Praktisk Teologi, 2020)
This article takes its starting point in a recent tendency to include care for creation in the interpretation of diaconia as a ministry of the Christian church. Among those who argue for a renewed care for our neighbor and for the earth as our common home, we find such diverse Christian leaders as Pope Francis and the bishops of the Lutheran Church of Sweden. The article relates these arguments to a feminist discussion on the present crisis of welfare and care in the Western world. Both social care and ecological systems are exhausted in a system where care and reproductive work is subordinated to market oriented goals of growth and increased consumption. In order for the understanding of diaconia to integrate a responsibility not only in relation to needy human beings, but also to ecological systems that are under serious threat, the article argues for the importance of relating to this wider discussion on the crisis of care within feminist social theory. Feminist social theory may thus enrich theology in order to guard social care as a basic aspect of a global eco-system.